Influence of Ki-67 and proliferating cell nuclear antigen expression on the biological behavior of ameloblastomas - Alberto Rodriguez-Archilla; Carmen M Barragan-Muñoz (Wolters Kluwer Medknow Publications, 2018)
Background: Ameloblastomas, the second-most common odontogenic tumors, are locally aggressive benign lesions that derive from cellular components of the enamel organ. Objective: The objective of the study is to assess the possible influence of cell proliferation markers Ki-67 and proliferating cell nuclear antigen (PCNA) on the biological behavior of ameloblastomas. Materials and Methods: A PubMed database search through February 2018, using the following medical subject headings (MeSH) terms were performed: "ameloblastoma" and ("Ki 67 antigen" or "proliferating cell nuclear antigen"). Selection Criteria: Studies with findings on cell proliferation markers in ameloblastoma. There were no restrictions regarding language or date of publication. Data Analysis: The data were analyzed using statistical software RevMan 5.3 (The Cochrane Collaboration, Oxford, UK). For continuous outcomes, the estimates of effects of an intervention were expressed as mean differences using the inverse variance method together with 95% confidence intervals. Results: Fourteen studies on cell proliferation markers in ameloblastoma were included in this meta-analysis. A greater significant Ki-67 expression in recurrent ameloblastomas (P < 0.01), in follicular type of solid/multicystic ameloblastomas (P < 0.05) and maxilla located ameloblastomas (P < 0.05) was found. In contrast, no significant influence of Ki-67 expression was observed in the following parameters: clinical type of ameloblastoma, histological type of unicystic ameloblastoma, age, gender, or size of the lesion. Finally, PCNA expression had no significant influence in any case. Conclusions: Ki-67 but not PCNA antigens seem to have an influence on the biological behavior of ameloblastomas.